'Quarantine Quatrains', Malcolm Guite (2020). Issue 1 (1st August 2021) - Gowar, Mick
Review of: Quarantine Quatrains, Malcolm Guite (2020)https://malcolmguite.wordpress.com/2020/05/02/the-quarantine-quatrains-the-complete-poem